Anti-glare laminate

By using a laminated structure of polycarbonate resin, high hardness resin layer and hard coating in the anti-glare laminate, the problem of excellent anti-glare and touch in the prior art is solved, efficient anti-glare and touch performance is achieved, and good shape stability is maintained in high temperature and high humidity environments.

CN114929479BActive Publication Date: 2025-04-08MITSUBISHI GAS CHEM CO INC +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180008294.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-16
Publication Date
2025-04-08
Estimated Expiration
2041-03-16

AI Technical Summary

Technical Problem

In the case of using polycarbonate resin, it is difficult to achieve an anti-glare laminate with excellent anti-glare properties and touch simultaneously.

Method used

Excellent performance in anti-glare and touch is achieved by forming a prescribed laminate structure including a base material layer containing a polycarbonate resin, a high hardness resin layer and a hard coating layer, and controlling the surface characteristics of the hard coating layer.

Benefits of technology

This technical method effectively improves the anti-glare and tactile properties of the anti-glare laminate, and maintains shape stability in high temperature and high humidity environments, with small warping changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003734605630000031
    Figure BDA0003734605630000031
  • Figure BDA0003734605630000032
    Figure BDA0003734605630000032
  • Figure BDA0003734605630000041
    Figure BDA0003734605630000041
Patent Text Reader

Abstract

The present invention provides an anti-glare laminate with excellent anti-glare properties and tactile feel. The anti-glare laminate is at least sequentially configured with a substrate layer containing a polycarbonate resin (a1), a high-hardness resin layer containing a high-hardness resin, and a hard coating layer, wherein the arithmetic mean roughness (Ra), maximum peak height (Rp), maximum valley depth (Rv), and skewness (Rsk) of the hard coating layer satisfy the following formulas (1) to (3), and the dynamic friction coefficient (μk) obtained by measuring the hard coating layer with a load of 50 g, a scanning speed of 10 mm / second, and a scanning distance of 90 mm using a tactile probe as the probe of the hard coating layer satisfies the following formula (4), 0.03<Ra<0.10(1), 0.15<Rp / Rv<0.30(2), ‑5.0<Rsk<‑2.0(3), 0.6<μk<0.7(4).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anti-glare laminate. More specifically, the present invention relates to an anti-glare laminate used as a front protection plate for a touch panel of an in-vehicle display device, a mobile terminal, a personal computer, a tablet PC, etc., and a front plate for OA equipment, a portable electronic device, a television, etc.

[0002] A protective plate or a front plate is provided in a liquid crystal display device for the purpose of protecting a liquid crystal panel, etc. A (meth)acrylic resin represented by polymethyl methacrylate (PMMA) is used in a protective plate or a front plate of a conventional liquid crystal display device.

[0003] For such a protective plate or front panel, usually due to the scattering and interference of light, an anti-glare treatment that can suppress the image from being reflected or reduce the reflectivity is sometimes implemented. In addition, the protective plate or front panel is operated with a finger, so the excellent touch when the hand touches is also taken seriously.

[0004] For example, Patent Document 1 describes an invention related to a touch panel having irregularities on the surface on the operator side. In this case, the static friction coefficient and the arithmetic mean roughness (Ra 2.5 ) satisfies the prescribed conditions. Thus, Patent Document 1 records that the device has outdoor anti-glare properties and excellent operability of the touch panel. It should be noted that Patent Document 1 more specifically records that a concave-convex layer coating liquid containing an acrylic monomer, organic particles and inorganic particles is coated on a triacetyl cellulose (TAC) film, and the obtained coating film is irradiated with ultraviolet rays to form a laminate of concave-convex layers.

[0005] In addition, when the front panel is used in a temperature and humidity environment exceeding 40°C such as in a car, it is desirable to have excellent shape stability in a high temperature and high humidity environment. For example, it is preferred that the change in warpage before and after exposure to an environment with a temperature of 85°C and a humidity of 85% is small.

[0006] Therefore, in recent years, polycarbonate resins have been widely used as protective plates or front plates from the perspectives of high impact resistance, heat resistance, secondary processability, lightness, and transparency.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2017 / 188186 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] An object of the present invention is to provide an anti-glare laminate having excellent anti-glare properties and touch when a polycarbonate resin is used.

[0012] Technical solutions for solving technical problems

[0013] The inventors of the present invention have conducted intensive research to solve the above technical problems. As a result, they have found that the above technical problems can be solved by forming a predetermined laminated structure including a substrate layer containing a polycarbonate resin, a high-hardness resin layer, and a hard coating layer, and controlling the surface of the hard coating layer, thereby completing the present invention. That is, the present invention is as follows.

[0014] <1> An anti-glare laminate comprising at least a substrate layer containing a polycarbonate resin (a1), a high-hardness resin layer containing a high-hardness resin, and a hard coating layer arranged in this order, wherein:

[0015] The arithmetic mean roughness (Ra), maximum peak height (Rp), maximum valley depth (Rv) and skewness (Rsk) of the hard coating satisfy the following equations (1) to (3):

[0016] 0.03<Ra<0.10 (1)

[0017] 0.15<Rp / Rv<0.30 (2)

[0018] -5.0<Rsk<-2.0 (3)

[0019] The dynamic friction coefficient (μk) measured by using a tactile contact as the contact of the hard coating at a load of 50 g, a scanning speed of 10 mm / sec, and a scanning distance of 90 mm satisfies the following formula (4):

[0020] 0.6<μk<0.7 (4).

[0021] <2> The anti-glare laminate according to <1>, wherein the reflectance of the hard coat layer including regular reflected light at a wavelength of 550 nm (SCI 550 ) and the reflectivity after removing the regular reflected light (SCE 550 ) satisfies the following formula (5):

[0022] 0.25<SCE 550 / SCI 550 <0.60 (5).

[0023] <3> The anti-glare laminate according to <1> or <2>, wherein the change in warpage of the anti-glare laminate after being kept in an environment at a temperature of 85° C. and a relative humidity of 85% for 120 hours is 350 μm or less.

[0024] <4> The anti-glare laminate according to any one of <1> to <3> above, wherein the high-hardness resin layer has a thickness of 10 to 250 μm.

[0025] <5> The anti-glare laminate according to any one of <1> to <4>, wherein the total thickness of the substrate layer and the high-hardness resin layer is 100 to 3,000 μm.

[0026] <6> The anti-glare laminate according to any one of <1> to <5> above, wherein the high-hardness resin (B) comprises at least one selected from the group consisting of resin (B1), resin (B2), resin (B3), resin (B4), resin (B5) and resin (B6),

[0027] The resin (B1) is a copolymer resin comprising a (meth)acrylate structural unit (a) represented by the following general formula (1) and an aliphatic vinyl structural unit (b) represented by the following general formula (2), wherein the total ratio of the (meth)acrylate structural unit (a) and the aliphatic vinyl structural unit (b) is 90 to 100 mol% of the total structural units of the copolymer resin, and the ratio of the (meth)acrylate structural unit (a) is 65 to 80 mol% of the total structural units of the copolymer resin, wherein:

[0028]

[0029] (Where R 1 is a hydrogen atom or a methyl group, R 2 is an alkyl group having 1 to 18 carbon atoms. )

[0030]

[0031] (Where R 3 is a hydrogen atom or a methyl group, R 4 It is a cyclohexyl group which may have a hydrocarbon group having 1 to 4 carbon atoms.

[0032] The resin (B2) comprises 35-65% by mass of the resin (B1) and 35-65% by mass of a styrene-unsaturated dicarboxylic acid copolymer (C). The styrene-unsaturated dicarboxylic acid copolymer (C) comprises 65-90% by mass of a styrene structural unit (c1) and 10-35% by mass of an unsaturated dicarboxylic anhydride structural unit (c2).

[0033] The resin (B3) comprises 55 to 10% by mass of a resin (D) containing a vinyl monomer and 45 to 90% by mass of a styrene-unsaturated dicarboxylic acid copolymer (E). The styrene-unsaturated dicarboxylic acid copolymer (E) comprises 50 to 80% by mass of a styrene structural unit (e1), 10 to 30% by mass of an unsaturated dicarboxylic acid structural unit (e2), and 5 to 30% by mass of a vinyl structural unit (e3).

[0034] The resin (B4) is a resin copolymer (G) comprising 5 to 20% by mass of a styrene structural unit, 70 to 90% by mass of a (meth)acrylate structural unit, and 5 to 20% by mass of an N-substituted maleimide structural unit, or an alloy of the resin copolymer (G) and a styrene-unsaturated dicarboxylic acid copolymer (E),

[0035] The resin (B5) comprises a structural unit (H) represented by the following general formula (3):

[0036]

[0037] The resin (B6) comprises 35 to 65% by mass of a resin (D) containing a vinyl monomer and 35 to 65% by mass of a styrene-unsaturated dicarboxylic acid copolymer (C). The styrene-unsaturated dicarboxylic acid copolymer (C) comprises 65 to 90% by mass of a styrene structural unit (c1) and 10 to 35% by mass of an unsaturated dicarboxylic anhydride structural unit (c2).

[0038] <7> The anti-glare laminate according to <6> above, wherein the resin (B5) is a copolymer further comprising a structural unit (J) represented by the following general formula (4),

[0039]

[0040] <8> The anti-glare laminate according to any one of <1> to <7>, wherein the hard coat layer does not contain organic particles and inorganic particles.

[0041] <9> The anti-glare laminate according to any one of <1> to <8>, wherein the polycarbonate resin (a1) contains a component derived from a monohydric phenol represented by the following general formula (5),

[0042]

[0043] (Where R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, R 6Each independently represents a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and n is an integer from 0 to 4, wherein the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms. ).

[0044] <10> An in-vehicle display device comprising the anti-glare laminate according to any one of <1> to <9> above.

[0045] <11> A touch panel front protection plate comprising the anti-glare laminate according to any one of <1> to <9> above.

[0046] <12> A front plate for OA equipment, portable electronic device, or television, comprising the anti-glare laminate according to any one of <1> to <9> above.

[0047] <13> A method for producing the anti-glare laminate according to any one of <1> to <9>, wherein:

[0048] The method comprises the step of transferring the concavo-convex shape by pressing a patterned PET film onto the surface of the hard coat layer.

[0049] Effects of the Invention

[0050] According to the present invention, when a polycarbonate resin is used, an anti-glare laminate having excellent anti-glare properties and touch can be provided. DETAILED DESCRIPTION

[0051] Hereinafter, the present invention will be described in detail with reference to production examples and embodiments, but the present invention is not limited to the production examples and embodiments, and can be modified in any manner as long as it does not greatly depart from the scope of the content of the present invention.

[0052] The anti-glare laminate according to the present embodiment includes at least a base layer containing a polycarbonate resin (a1), a high-hardness resin layer containing a high-hardness resin, and a hard coat layer, which are arranged in this order.

[0053] The lamination order of the anti-glare laminate is preferably substrate layer-high hardness resin layer-hard coating layer. The other surface of the substrate layer is not particularly specified. In one embodiment, a high hardness resin layer may be provided on the other surface of the substrate layer. In this case, the anti-glare laminate has a structure of high hardness resin layer-substrate layer-high hardness resin layer-hard coating layer. In addition, in one embodiment, a high hardness resin layer and a hard coating layer may be provided on the other surface of the substrate layer. In this case, the anti-glare laminate has a structure of hard coating layer-high hardness resin layer-substrate layer-high hardness resin layer-hard coating layer.

[0054] When the high hardness resin layer is disposed on both surfaces of the substrate layer, it is more desirable to use the same high hardness resin layer on both surfaces for shape stability. In addition, when the hard coating layer is disposed on both surfaces of the substrate, it is more desirable to provide the same hard coating layer on both surfaces from the perspective of good shape stability. It should be noted that the substrate layer and the high hardness resin layer, the high hardness resin layer and the hard coating layer can be laminated directly or through other layers, preferably directly laminated.

[0055] In one embodiment, the anti-glare laminate can be used, for example, for car navigation, central information display (CID), rear seat entertainment system (RSE), instrument, etc., as a vehicle-mounted display device, a touch panel full protection plate, and a front panel for OA equipment, portable electronic devices, and televisions. In addition, for example, the front panel can be used alone as a front panel of a liquid crystal display device, or it can be used as a front panel after being laminated with other substrates such as a touch sensor.

[0056] Hereinafter, each component of the anti-glare laminate of the present invention will be described.

[0057] <Base material layer>

[0058] The base material layer contains the polycarbonate resin (a1). The base material layer may further contain additives and the like.

[0059] [Polycarbonate resin (a1)]

[0060] The polycarbonate resin (al) is not particularly limited as long as it contains a carbonate bond, i.e., -[O-R-OCO]- unit in the main chain of the molecule (R may contain an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and may have a linear structure or a branched structure). It is particularly preferred to use a polycarbonate resin containing a structural unit of the following formula (4). By using such a polycarbonate resin, a resin laminate having excellent impact resistance can be obtained.

[0061]

[0062] Specifically, as the polycarbonate resin (a1), an aromatic polycarbonate resin (for example, manufactured by Mitsubishi Engineering-Plastics Corporation, trade names: Iupilon S-2000, Iupilon S-1000, Iupilon E-2000) etc. can be used, but the present invention is not limited thereto.

[0063] In recent years, there has been an increasing demand for bending of the front panel, and therefore, as the polycarbonate resin (a1), it is preferred that a monophenol represented by the following general formula (5) be used as a terminal terminator.

[0064]

[0065] In the formula, R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, R 6 Each independently represents a hydrogen atom, a halogen, an alkyl group having 1 to 20 carbon atoms which may have a substituent, or an aryl group having 6 to 12 carbon atoms, and n is an integer of 0 to 4, wherein the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms. It should be noted that in the present specification, "alkyl" and "alkenyl" may be linear or branched, and may have a substituent.

[0066] More preferably, the monohydric phenol represented by the general formula (5) is represented by the following general formula (6).

[0067]

[0068] In the formula, R 5 It represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms.

[0069] In the general formula (5) or (6), R 5 The number of carbon atoms in R is preferably within a specific numerical range. 5 The upper limit of the number of carbon atoms is preferably 36, more preferably 22, and particularly preferably 18. 5 The lower limit of the number of carbon atoms is preferably 8, and more preferably 12.

[0070] In the general formula (5) or (6), R 5 When the upper limit of the number of carbon atoms is appropriate, the solubility of the monohydric phenol (terminator) in an organic solvent tends to be high, and the productivity in producing the polycarbonate resin is improved, which is preferred.

[0071] As an example, R 5 When the number of carbon atoms is 36 or less, the productivity is high and the economic efficiency is good when producing a polycarbonate resin. 5 When the carbon number of the monohydric phenol is 22 or less, the solubility of the monohydric phenol in an organic solvent is particularly excellent, and when the polycarbonate resin is produced, the productivity can be made very high, and the economic efficiency is also improved.

[0072] In the general formula (5) or (6), R 5 When the lower limit of the number of carbon atoms is appropriate, the glass transition temperature of the polycarbonate resin will not be too high and appropriate thermoformability will be achieved, which is preferred.

[0073] For example, when using R in the general formula (6) 5In the case of a monophenol (terminator) having an alkyl group with 16 carbon atoms, the monophenol has excellent glass transition temperature, melt fluidity, moldability, drawdown resistance, and solvent solubility during the production of the polycarbonate resin, and is particularly preferred as the terminator used for the polycarbonate resin of the present invention.

[0074] Among the monohydric phenols (terminator) represented by the general formula (5) or (6), it is particularly preferable to use either or both of hexadecyl p-hydroxybenzoate and 2-hexyldecyl p-hydroxybenzoate as the terminator.

[0075] The weight average molecular weight of the polycarbonate resin (a1) is preferably 15,000 to 75,000, more preferably 20,000 to 70,000, and further preferably 20,000 to 65,000. When the weight average molecular weight of the polycarbonate resin (a1) is 15,000 or more, the impact resistance can be increased, so it is preferred. On the other hand, when the weight average molecular weight is 75,000 or less, the substrate layer can be formed using a small heat source, and even when the molding conditions become high temperature, thermal stability can be maintained, so it is preferred. It should be noted that in this specification, the weight average molecular weight is the weight average molecular weight converted to standard polystyrene measured by gel permeation chromatography (GPC).

[0076] The polycarbonate resin (a1) contained in the base material layer may be one kind or two or more kinds.

[0077] The content of the polycarbonate resin (a1) in the substrate layer is preferably 75% by mass or more, more preferably 90% by mass or more, and further preferably 100% by mass, based on the total mass of the substrate layer, from the viewpoint of improving impact resistance.

[0078] [additive]

[0079] The base material layer may further contain additives.

[0080] As additives, additives commonly used in anti-glare laminates can be used. As additives, for example, antioxidants, anti-coloring agents, antistatic agents, release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, compatibilizers, reinforcing materials such as organic particles and inorganic particles can be listed.

[0081] The amount of the additive is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and particularly preferably 0 to 5% by mass, based on the total mass of the base material layer.

[0082] The method of mixing the additives and the resin is not particularly limited, and a method of mixing the entire amount, a method of dry-blending a master batch, a method of dry-blending the entire amount, etc. can be used.

[0083] [Constitution of base material layer]

[0084] The thickness of the substrate layer is preferably 0.3 to 10 mm, more preferably 0.3 to 5 mm, and particularly preferably 0.3 to 3.5 mm.

[0085] <High hardness resin layer>

[0086] The high hardness resin layer contains a high hardness resin. In addition, the high hardness resin layer may also contain additives as needed. The high hardness resin layer is disposed between the substrate layer and the hard coating layer, thereby being able to obtain an anti-glare laminate having high shape stability. In addition, the high hardness resin layer may have a function of increasing the hardness of the anti-glare laminate, etc. It should be noted that in this specification, the high hardness resin is a resin having a higher hardness than the polycarbonate resin as the substrate, and refers to a resin having a pencil hardness of HB or more, preferably HB to 3H, more preferably H to 3H, and further preferably 2H to 3H. It should be noted that the pencil hardness of the high hardness resin layer is the result of evaluation using a pencil scratch hardness test based on JIS K 5600-5-4:1999. Specifically, for the surface of the hard coating layer, the hardness is gradually increased at an angle of 45 degrees and a load of 750g, and the pencil is pressed, and the hardest pencil hardness that does not produce scratches is evaluated as the pencil hardness.

[0087] [High hardness resin]

[0088] The high hardness resin is not particularly limited, but preferably contains at least one selected from resins (B1) to (B6). It should be noted that resins (B1) to (B6) are sometimes referred to as resins (B1) to (B6) even when they are resin compositions containing a plurality of resins.

[0089] (Resin (B1))

[0090] Resin (B1) is a copolymer resin comprising a (meth)acrylate structural unit (a) represented by general formula (1) and an aliphatic vinyl structural unit (b) represented by general formula (2). At this time, the above-mentioned resin (B1) (copolymer resin) may also have other structural units. Among them, the total ratio of the above-mentioned (meth)acrylate structural unit (a) and the above-mentioned aliphatic vinyl structural unit (b) is 90 to 100 mol% of the total structural units of the above-mentioned copolymer resin, preferably 95 to 100 mol%, and more preferably 98 to 100 mol%. In addition, the ratio of the above-mentioned (meth)acrylate structural unit (a) is 65 to 80 mol% of the total structural units of the above-mentioned copolymer resin. It should be noted that in this specification, (meth)acrylic acid represents methacrylic acid and / or acrylic acid.

[0091]

[0092] In the formula, R 1 It is a hydrogen atom or a methyl group, and is preferably a methyl group.

[0093] In addition, R 2 It is an alkyl group having 1 to 18 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms. Specific examples thereof include methyl, ethyl, butyl, lauryl, stearyl, cyclohexyl, and isobornyl. Among these, R 2 Preferred are methyl and ethyl, and more preferred are methyl.

[0094] Among them, in R 2 When R is methyl or ethyl, the (meth)acrylate structural unit (a) represented by the general formula (1) is a (meth)acrylate structural unit. 1 is methyl and R 2 When it is a methyl group, the (meth)acrylate structural unit (a) represented by the general formula (1) is a methyl methacrylate structural unit.

[0095] The (meth)acrylate structural unit (a) represented by the general formula (1) may be contained in the resin (B1) alone or in combination of two or more.

[0096]

[0097] In the formula, R 3 It is a hydrogen atom or a methyl group, and is preferably a hydrogen atom.

[0098] R 4 It is a cyclohexyl group which may be substituted by a hydrocarbon group having 1 to 4 carbon atoms, and preferably a cyclohexyl group which has no substituent. It should be noted that in the present specification, the "hydrocarbon group" may be linear, branched, or cyclic, and may have a substituent.

[0099] In R 3 is a hydrogen atom and R 4 In the case of a cyclohexyl group, the aliphatic vinyl structural unit (b) represented by the general formula (2) is a vinylcyclohexane structural unit.

[0100] The resin (B1) may contain only one kind of the aliphatic vinyl structural unit (b) represented by the general formula (2), or may contain two or more kinds of the aliphatic vinyl structural unit (b).

[0101] The other structural units are not particularly limited, and examples thereof include structural units derived from aromatic vinyl monomers containing unhydrogenated aromatic double bonds produced in a process of polymerizing a (meth)acrylate monomer and an aromatic vinyl monomer and then hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer to produce resin (B1). Specific examples of the other structural units include styrene structural units.

[0102] The resin (B1) may contain only one type of other structural units, or may contain two or more types.

[0103] The total ratio of the (meth)acrylate structural unit (a) and the aliphatic vinyl structural unit (b) is 90 to 100 mol %, preferably 95 to 100 mol %, and more preferably 98 to 100 mol % based on the total of all structural units of the resin (B1) (copolymer resin).

[0104] In addition, the content of the (meth)acrylate structural unit (a) represented by the general formula (1) is 65 to 80 mol%, preferably 70 to 80 mol%, relative to the total structural units of the above-mentioned resin (B1) (copolymer resin). When the content of the (meth)acrylate structural unit (a) is 65 mol% or more, a resin layer having excellent adhesion to the substrate layer and surface hardness can be obtained. On the other hand, when the content of the (meth)acrylate structural unit (a) is 80 mol% or less, the anti-glare laminated body will not warp due to water absorption, so it is preferred.

[0105] In addition, the content of the aliphatic vinyl structural unit (b) represented by the general formula (2) is preferably 20 to 35 mol%, more preferably 20 to 30 mol%, relative to the total structural units of the resin (B1) (copolymer resin). When the content of the aliphatic vinyl structural unit (b) is 20 mol% or more, it is possible to prevent warping under high temperature and high humidity, and thus it is preferred. On the other hand, when the content of the aliphatic vinyl structural unit (b) is 35 mol% or less, it is possible to prevent peeling at the interface with the substrate, and thus it is preferred.

[0106] The content of the other structural units is preferably 10 mol% or less, more preferably 5 mol% or less, particularly preferably 2 mol% or less, based on the total structural units of the resin (B1) (copolymer).

[0107] It should be noted that, in the present specification, the "copolymer" may have any structure of a random, block or alternating copolymer.

[0108] The weight average molecular weight of the resin (B1) is not particularly limited, but is preferably 50,000 to 400,000, more preferably 70,000 to 300,000, from the viewpoint of strength and moldability.

[0109] The glass transition temperature of resin (B1) is preferably 110 to 140°C, more preferably 110 to 135°C, and particularly preferably 110 to 130°C. When the glass transition temperature is 110°C or higher, the resin sheet is less likely to deform and crack in a hot environment or a hot and humid environment, so it is preferred. On the other hand, when it is 140°C or lower, it is preferred because the processability is excellent when molding is performed by continuous heat forming using a mirror roller and a shaping roller, or intermittent heat forming using a mirror mold and a shaping mold. It should be noted that the glass transition temperature in the present invention is a temperature measured using a differential scanning calorimeter with a sample of 10 mg and a heating rate of 10°C / min and calculated using the midpoint method.

[0110] Specific examples of the resin (B1) include Optimas 7500 and 6000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) The resin (B1) may be used alone or in combination of two or more.

[0111] The method for producing the resin composition (B1) is not particularly limited, but a compound obtained by polymerizing at least one (meth)acrylate monomer and at least one aromatic vinyl monomer and then hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer is preferred.

[0112] The aromatic vinyl monomer is not particularly limited, and examples thereof include styrene, α-methylstyrene, p-hydroxystyrene, alkoxystyrene, chlorostyrene, and derivatives thereof. Among these, the aromatic vinyl monomer is preferably styrene.

[0113] The (meth)acrylate monomer and the aromatic vinyl monomer can be polymerized by a known method, for example, bulk polymerization or solution polymerization.

[0114] The bulk polymerization can be carried out by a method in which a monomer composition containing the above-mentioned monomers and a polymerization initiator is continuously supplied to a complete mixing tank and continuously polymerized at 100 to 180° C. The above-mentioned monomer composition may contain a chain transfer agent as required.

[0115] The polymerization initiator is not particularly limited, and examples thereof include organic peroxides such as tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, benzoyl peroxide, 1,1-di(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, tert-hexylpropoxyisopropylmonocarbonate, tert-amyl peroxyoctanoate, tert-butylperoxyisopropylmonocarbonate, and di-tert-butyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile). These may be used alone or in combination of two or more.

[0116] The chain transfer agent is not particularly limited, and an α-methylstyrene dimer may be mentioned.

[0117] Examples of the solvent used in the solution polymerization method include hydrocarbon solvents such as toluene, xylene, cyclohexane, and methylcyclohexane; ester solvents such as ethyl acetate and methyl isobutyrate; ketone solvents such as acetone and methyl ethyl ketone; ether solvents such as tetrahydrofuran and dioxane; and alcohol solvents such as methanol and isopropanol. These solvents may be used alone or in combination of two or more.

[0118] The solvent used in the hydrogenation reaction after polymerization of the (meth)acrylate monomer and the aromatic vinyl monomer may be the same as or different from the above-mentioned polymerization solvent. Examples thereof include hydrocarbon solvents such as cyclohexane and methylcyclohexane; ester solvents such as ethyl acetate and methyl isobutyrate; ketone solvents such as acetone and methyl ethyl ketone; ether solvents such as tetrahydrofuran and dioxane; and alcohol solvents such as methanol and isopropanol.

[0119] The resin (B1) can be obtained by polymerizing the (meth)acrylic acid ester monomer and the aromatic vinyl monomer as described above and then hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer.

[0120] The method of hydrogenation is not particularly limited, and a known method can be used. For example, it can be carried out in an intermittent or continuous flow manner at a hydrogen pressure of 3 to 30 MPa and a reaction temperature of 60 to 250° C. When the temperature is 60° C. or higher, the reaction time will not be too long, so it is preferred. On the other hand, when the reaction temperature is 250° C. or lower, side reactions such as molecular chain severance or hydrogenation of the ester portion will not occur or will hardly occur, so it is preferred.

[0121] Examples of the catalyst used for the hydrogenation reaction include solid catalysts obtained by supporting metals such as nickel, palladium, platinum, cobalt, ruthenium, and rhodium, or oxides, salts, or coordination compounds of these metals on porous carriers such as carbon, alumina, silica, silica / alumina, and diatomaceous earth.

[0122] By hydrogenation reaction, the aromatic double bonds from the aromatic vinyl monomer are preferably hydrogenated by more than 70%. That is, the unhydrogenated rate of the aromatic double bonds contained in the structural units from the aromatic vinyl monomer is preferably less than 30%, more preferably less than 10%, and further preferably less than 5%. When the unhydrogenated rate is less than 30%, a resin with excellent transparency can be obtained, which is preferred. It should be noted that the structural units of the unhydrogenated part can be other structural units in the resin (B1).

[0123] The resin (B1) may be blended with other resins within a range that does not impair transparency. That is, the resin (B1) is a resin composition containing the copolymer and other resins. Examples of the other resins include methyl methacrylate-styrene copolymer resins, polymethyl methacrylate, polystyrene, polycarbonate, cycloolefin (co)polymer resins, acrylonitrile-styrene copolymer resins, acrylonitrile-butadiene-styrene copolymer resins, and various elastomers.

[0124] (Resin (B2))

[0125] The resin (B2) comprises 35 to 65% by mass, preferably 40 to 60% by mass, of the resin (B1) and 35 to 65% by mass, preferably 40 to 60% by mass, of a styrene-unsaturated dicarboxylic acid copolymer (C). In addition, the styrene-unsaturated dicarboxylic acid copolymer (C) comprises 65 to 90% by mass of a styrene-based structural unit (c1) and 10 to 35% by mass of an unsaturated dicarboxylic anhydride structural unit (c2). That is, the resin (B2) is a resin composition containing two or more resins. The content of the resin (B1) and the content of the styrene-unsaturated dicarboxylic acid copolymer (C) are the contents relative to the total mass of the resin (B2).

[0126] Resin (B1)

[0127] As the resin (B1), the above-mentioned resin (B1) can be used. In this case, the resin (B1) may be used alone or in combination of two or more.

[0128] ·Styrene-unsaturated dicarboxylic acid copolymer (C)

[0129] The styrene-unsaturated dicarboxylic acid copolymer (C) contains a styrene-based structural unit (c1) and an unsaturated dicarboxylic anhydride structural unit (c2).

[0130] Styrene structural unit (c1)

[0131] As styrene monomers, there is no particular limitation, and any known styrene monomers can be used. As specific examples of styrene monomers, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. can be cited. Among these, styrene is particularly preferred from the viewpoint of compatibility. These styrene monomers can be used alone or in combination of two or more.

[0132] The content of the styrene structural unit (c1) is 65 to 90% by mass, preferably 70 to 85% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (C).

[0133] Unsaturated dicarboxylic anhydride structural unit (c2)

[0134] As unsaturated dicarboxylic anhydride monomer, there is no particular limitation, and examples thereof include anhydrides of maleic acid, itaconic acid, citraconic acid, aconitic acid, etc. Among these, maleic anhydride is preferred from the viewpoint of compatibility with styrene monomers. These unsaturated dicarboxylic anhydride monomers can be used alone or in combination of two or more.

[0135] The content of the unsaturated dicarboxylic acid anhydride structural unit (c2) is 10 to 35% by mass, preferably 15 to 30% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (C).

[0136] Specific examples of the styrene-unsaturated dicarboxylic acid copolymer (C) include XIBOND140, XIBOND160, XIRAN SO23110, and XIRAN SO26080 (manufactured by Polyscope Co., Ltd.) These styrene-unsaturated dicarboxylic acid copolymers (C) may be used alone or in combination of two or more.

[0137] (Resin (B3))

[0138] Resin (B3) includes 55 to 10% by mass of a resin (D) containing a vinyl monomer and 45 to 90% by mass of a styrene-unsaturated dicarboxylic acid copolymer (E). In addition, the styrene-unsaturated dicarboxylic acid copolymer (E) includes 50 to 80% by mass of a styrene structural unit (e1), 10 to 30% by mass of an unsaturated dicarboxylic acid structural unit (e2), and 5 to 30% by mass of a vinyl structural unit (e3). That is, resin (B3) is a resin composition containing two or more resins. It should be noted that the content of the resin (D) containing a vinyl monomer and the content of the styrene-unsaturated dicarboxylic acid copolymer (E) are relative to the total mass of the resin (B3).

[0139] ·Resin containing vinyl monomer (D)

[0140] The resin (D) containing a vinyl monomer is not particularly limited, and examples thereof include polymers obtained by polymerizing vinyl monomers such as acrylonitrile, methacrylonitrile, acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate. Among these, the resin (D) containing a vinyl monomer preferably contains methyl methacrylate as a structural unit. The resin (D) containing a vinyl monomer may be a polymer using one of the above structural units, or a copolymer using two or more of the above structural units in combination.

[0141] The weight average molecular weight of the resin (D) containing a vinyl monomer is preferably 10,000 to 500,000, more preferably 50,000 to 300,000.

[0142] The above-mentioned resin (D) containing a vinyl monomer may be used alone or in combination of two or more.

[0143] ·Styrene-unsaturated dicarboxylic acid copolymer (E)

[0144] The styrene-unsaturated dicarboxylic acid copolymer (E) contains a styrene structural unit (e1), an unsaturated dicarboxylic anhydride structural unit (e2), and a vinyl structural unit (e3).

[0145] Styrene structural unit (e1)

[0146] As styrene monomers, there is no particular limitation, and any known styrene monomers can be used. As specific examples of styrene monomers, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. can be cited. Among these, styrene is particularly preferred from the viewpoint of compatibility. These styrene monomers can be used alone or in combination of two or more.

[0147] The content of the styrene structural unit (e1) is 50 to 80% by mass, preferably 50 to 75% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (E).

[0148] Unsaturated dicarboxylic anhydride structural unit (e2)

[0149] As unsaturated dicarboxylic anhydride monomer, there is no particular limitation, and examples thereof include anhydrides of maleic acid, itaconic acid, citraconic acid, aconitic acid, etc. Among these, maleic anhydride is preferred from the viewpoint of compatibility with vinyl monomers. These unsaturated dicarboxylic anhydride monomers can be used alone or in combination of two or more.

[0150] The content of the unsaturated dicarboxylic acid anhydride structural unit (e2) is 10 to 30% by mass, preferably 10 to 25% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (E).

[0151] Vinyl structural unit (e3)

[0152] As the vinyl monomer, there is no particular limitation, and examples thereof include acrylonitrile, methacrylonitrile, acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate and the like. Among these, methyl methacrylate (MMA) is preferred from the viewpoint of compatibility with the resin (D) containing the vinyl monomer. These vinyl monomers may be used alone or in combination of two or more.

[0153] The content of the vinyl structural unit (e3) is 5 to 30% by mass, preferably 7 to 27% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (E).

[0154] The weight average molecular weight of the styrene-unsaturated dicarboxylic acid copolymer (E) is preferably 50,000 to 200,000, more preferably 80,000 to 200,000. The weight average molecular weight within the above range is preferred because the compatibility with the resin (D) containing a vinyl monomer is good and the effect of improving heat resistance is excellent.

[0155] Specific examples of the styrene-unsaturated dicarboxylic acid copolymer (E) include, but are not limited to, RESISFY R100, R200, R310 (manufactured by Denki Kagaku Kogyo Co., Ltd.), DELPET980N (manufactured by Asahi Kasei Co., Ltd.) and the like. The above-mentioned styrene-unsaturated dicarboxylic acid copolymer (E) may be used alone or in combination of two or more thereof.

[0156] (Resin (B4))

[0157] The resin (B4) is a resin copolymer (G) containing 5 to 20% by mass of a styrene structural unit, 70 to 90% by mass of a (meth)acrylate structural unit, and 5 to 20% by mass of an N-substituted maleimide structural unit, or an alloy of the resin copolymer (G) and a styrene-unsaturated dicarboxylic acid copolymer (E).

[0158] ·Resin copolymer (G)

[0159] The resin copolymer (G) contains a styrene structural unit, a (meth)acrylate structural unit, and an N-substituted maleimide structural unit.

[0160] Styrene structural unit

[0161] As styrene monomers, there is no particular limitation, and any known styrene monomers can be used. As specific examples of styrene monomers, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. can be cited. Among these, styrene is particularly preferred from the viewpoint of compatibility. These styrene monomers can be used alone or in combination of two or more.

[0162] The content of the styrene structural unit is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass, based on the total mass of the resin (B4) (resin copolymer (G)).

[0163] (Meth)acrylate structural unit

[0164] The (meth)acrylate monomer is not particularly limited, and examples thereof include acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, etc. Among these, methyl methacrylate is preferred. These (meth)acrylate monomers may be used alone or in combination of two or more.

[0165] The content of the (meth)acrylate structural unit is 60 to 90% by mass, preferably 70 to 90% by mass, and more preferably 80 to 90% by mass, based on the total mass of the resin (B4) (resin copolymer (G)).

[0166] N-substituted maleimide structural unit

[0167] As N-substituted maleimide monomers, there are no particular restrictions, and examples thereof include N-phenylmaleimide, N-chlorophenylmaleimide, N-methylphenylmaleimide, N-naphthylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-carboxyphenylmaleimide, N-nitrophenylmaleimide, N-tribromophenylmaleimide and other N-arylmaleimides. Among these, N-phenylmaleimide is preferred from the viewpoint of compatibility with the (meth)acrylic acid structural unit. Among these, these N-substituted maleimide monomers may be used alone or in combination of two or more.

[0168] The content of the N-substituted maleimide structural unit is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass, based on the total mass of the resin (B4) (resin copolymer (G)).

[0169] The weight average molecular weight of the resin copolymer (G) is preferably 50,000 to 250,000, more preferably 100,000 to 200,000.

[0170] Specific examples of the resin copolymer (G) include DELPET PM120N (manufactured by Asahi Kasei Chemicals Corporation), but the present invention is not limited to this.

[0171] The method for producing the resin copolymer (G) is not particularly limited, and the resin copolymer (G) can be produced by solution polymerization, bulk polymerization, or the like.

[0172] ·alloy

[0173] The alloy is an alloy of the resin copolymer (G) and the styrene-unsaturated dicarboxylic acid copolymer (E).

[0174] In this case, the resin copolymer (G) and the styrene-unsaturated dicarboxylic acid copolymer (E) are preferably alloys of copolymers having high glass transition temperatures.

[0175] The method for producing the alloy is not particularly limited, and examples thereof include a method in which melt kneading is performed using a twin-screw extruder having a screw diameter of 26 mm at a barrel temperature of 240° C., the mixture is extruded into a strand shape, and pelletized using a pelletizer.

[0176] (Resin (B5))

[0177] The resin (B5) contains the structural unit (H) represented by the general formula (3). The resin (B5) is preferably a copolymer further containing the structural unit (J) represented by the general formula (4). In addition, the above polymer may further contain other structural units.

[0178]

[0179] The content of the structural unit (H) represented by the general formula (3) is preferably 50 to 100 mol %, more preferably 60 to 100 mol %, and even more preferably 70 to 100 mol % based on the total structural units of the resin (B5).

[0180]

[0181] The content of the structural unit (J) represented by the general formula (4) is preferably 0 to 50 mol %, more preferably 0 to 40 mol %, and even more preferably 0 to 30 mol % based on the total structural units of the resin (B5).

[0182] The content of other structural units is preferably 10 mol% or less, more preferably 5 mol% or less, particularly preferably 2 mol% or less, based on all structural units of the resin (B5).

[0183] The total content of the structural units (H) and (J) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and even more preferably 98 to 100 mol % based on all the structural units of the resin (B5).

[0184] The weight average molecular weight of the resin (B5) is preferably 15,000 to 75,000, more preferably 20,000 to 70,000, particularly preferably 25,000 to 65,000.

[0185] Specific examples of the resin (B5) include Iupilon KH3410UR, KH3520UR, and KS3410UR (manufactured by Mitsubishi Engineering-Plastics Corporation), but the present invention is not limited thereto. The above resin (B5) may be used alone or in combination of two or more.

[0186] The method for producing the resin composition (B5) is not particularly limited, and the resin composition (B5) can be produced by the same method as the method for producing the polycarbonate resin (a1) described above, except that bisphenol C is used as a monomer.

[0187] (Resin (B6))

[0188] Resin (B6) contains 35-65% by mass of resin (D) containing vinyl monomers and 35-65% by mass of styrene-unsaturated dicarboxylic acid copolymer (C). In addition, the above-mentioned styrene-unsaturated dicarboxylic acid copolymer (C) contains 65-90% by mass of styrene structural units (c1) and 10-35% by mass of unsaturated dicarboxylic anhydride structural units (c2). That is, resin (B6) is a resin composition containing two or more resins. It should be noted that the content of the above-mentioned resin (D) containing vinyl monomers and the content of the styrene-unsaturated dicarboxylic acid copolymer (C) are the contents relative to the total mass of resin (B6).

[0189] ·Resin containing vinyl monomer (D)

[0190] As the resin (D) containing a vinyl monomer, the same resin as described above for the resin (B3) can be used. The resin (D) containing a vinyl monomer can be used alone or in combination of two or more.

[0191] ·Styrene-unsaturated dicarboxylic acid copolymer (C)

[0192] As the styrene-unsaturated dicarboxylic acid copolymer (C), the same copolymer as described above for the resin (B2) can be used. The styrene-unsaturated dicarboxylic acid copolymer (C) may be used alone or in combination of two or more.

[0193] By including at least one selected from the above-mentioned resins (B1) to (B6) as the high-hardness resin, an anti-glare laminate having more excellent shape stability under high temperature and high humidity can be obtained, which is preferred.

[0194] [additive]

[0195] The high-hardness resin layer may contain additives.

[0196] As the above-mentioned additive, there is no particular restriction, and additives commonly used in the anti-glare laminate can be used. As specific examples, antioxidants, anti-coloring agents, antistatic agents, release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, compatibilizers, reinforcing materials such as organic particles and inorganic particles can be listed.

[0197] The amount of the additive is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and particularly preferably 0 to 5% by mass, based on the total mass of the high-hardness resin layer.

[0198] The method of mixing the additives and the resin is not particularly limited, and a method of mixing the entire amount, a method of dry-blending a master batch, a method of dry-blending the entire amount, etc. can be used.

[0199] [Constitution of high hardness resin layer]

[0200] The thickness of the high hardness resin layer is preferably 10 to 250 μm, more preferably 30 to 200 μm, and particularly preferably 60 to 150 μm. When the thickness of the high hardness resin layer is 10 μm or more, the surface hardness becomes high, which is preferred. On the other hand, when the thickness of the high hardness resin layer is 250 μm or less, the impact resistance becomes high, which is preferred.

[0201] [Lamination of high hardness resin layer onto base material layer]

[0202] As described above, another layer may be present between the base material layer and the high hardness resin layer. Here, a case where the high hardness resin layer is laminated on the base material layer will be described.

[0203] The total thickness of the substrate layer and the high hardness resin layer is preferably 100 to 3500 μm, more preferably 100 to 3000 μm, further preferably 500 to 3000 μm, and particularly preferably 1200 to 3000 μm. When the total thickness is 100 μm or more, the rigidity of the sheet can be maintained, which is preferred. On the other hand, when the total thickness is 3500 μm or less, when a touch panel is provided under the sheet, etc., the sensitivity of the touch sensor can be prevented from being deteriorated, which is preferred.

[0204] The thickness of the substrate layer accounts for preferably 75% to 99% of the total thickness of the substrate layer and the high-hardness resin layer, more preferably 80% to 99%, and particularly preferably 85% to 99%. By being within the above range, both hardness and impact resistance can be achieved.

[0205] The method of laminating the high-hardness resin layer on the substrate layer is not particularly limited, and examples thereof include: a method of overlapping the substrate layer and the high-hardness resin layer formed separately and heat-pressing the two; a method of overlapping the substrate layer and the high-hardness resin layer formed separately and bonding the two using an adhesive; a method of co-extruding the substrate layer and the high-hardness resin layer; a method of in-mold molding and integrating the substrate layer on the pre-formed high-hardness resin layer, etc. Among these, the co-extrusion molding method is preferred from the viewpoint of manufacturing cost and productivity.

[0206] The co-extrusion method is not particularly limited. For example, in the feed block method, a high-hardness resin layer is arranged on one surface of the substrate layer using a feed block, and after being extruded into a sheet using a T-die, it is cooled while passing through a molding roller to form a desired laminate. In addition, in the multi-flow channel method, a high-hardness resin layer is arranged on one surface of the substrate layer in a multi-flow channel die, and after being extruded into a sheet, it is cooled while passing through a molding roller to form a desired laminate.

[0207] <Hard coating>

[0208] There are no particular restrictions on the hard coating layer, but an acrylic hard coating layer is preferred. It should be noted that in this specification, "acrylic hard coating layer" refers to a coating film obtained by polymerizing a monomer or oligomer or prepolymer containing a (meth)acryloyl group as a polymerizable group to form a cross-linked structure. The hard coating layer may also contain a UV absorber.

[0209] The above-mentioned hard coating preferably does not contain organic particles and inorganic particles. By not containing organic particles and inorganic particles, it is possible to improve scratch resistance. In addition, as described later, the transfer using a mold is used to carry out the anti-glare treatment of the hard coating, thus can not contain organic particles and inorganic particles and form a hard coating with a concavo-convex shape.

[0210] The content of the (meth)acrylic monomer is preferably 2 to 98% by mass, more preferably 5 to 50% by mass, and even more preferably 20 to 40% by mass, based on the total mass of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier.

[0211] The content of the (meth)acrylic oligomer is preferably 2 to 98% by mass, more preferably 50 to 95% by mass, and even more preferably 60 to 80% by mass, based on the total mass of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier.

[0212] The content of the surface modifier is preferably 0 to 15% by mass, more preferably 1 to 10% by mass, and even more preferably 2 to 5% by mass, based on the total mass of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier.

[0213] In addition, when a photopolymerization agent is contained, the content of the photopolymerization agent is preferably 0.001 to 7 parts by mass, more preferably 0.01 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the total of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier. It should be noted that in this specification, the photopolymerization initiator refers to a photo radical generator.

[0214] [(Meth)acrylic acid monomer]

[0215] As the (meth)acrylic monomer, any monomer having a (meth)acryloyl group as a functional group in the molecule can be used, and specific examples thereof include monofunctional monomers, difunctional monomers, and trifunctional or higher-functional monomers.

[0216] Examples of the monofunctional monomer include (meth)acrylic acid and (meth)acrylate esters.

[0217] Specific examples of the bifunctional and / or trifunctional or higher (meth)acrylic monomers include diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, tetraethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol diacrylate, dipentyl glycol di(meth)acrylate, 1,4-butylene glycol diacrylate, 1,3-butylene glycol di(meth)acrylate, di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate. Dicyclopentane acrylate, polyethylene glycol diacrylate, oligomeric acrylate-1,4-butylene glycol, oligomeric acrylate-neopentyl glycol, oligomeric acrylate-1,6-hexanediol, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, trimethylolpropane propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glyceryl propoxy tri(meth)acrylate, trimethylolpropane trimethacrylate, trimethylolpropane ethylene oxide adduct triacrylate, glycerol propylene oxide adduct triacrylate, pentaerythritol tetraacrylate, etc.

[0218] The hard coat layer may contain one or two or more (meth)acrylic monomers.

[0219] [(Meth)acrylic acid oligomer]

[0220] Examples of (meth)acrylic oligomers include polyfunctional urethane (meth)acrylate oligomers having two or more functionalities (hereinafter also referred to as “polyfunctional urethane (meth)acrylate oligomers”), polyfunctional polyester (meth)acrylate oligomers having two or more functionalities (hereinafter also referred to as “polyfunctional polyester (meth)acrylate oligomers”), and polyfunctional epoxy (meth)acrylate oligomers having two or more functionalities (hereinafter also referred to as “polyfunctional epoxy (meth)acrylate oligomers”).

[0221] Examples of the multifunctional polyurethane (meth)acrylate oligomer include: an amine reaction product of a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule and a polyisocyanate; an amine reaction product of an isocyanate compound obtained by reacting a polyol with a polyisocyanate and a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule; and the like.

[0222] Examples of the (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule used for the amination reaction include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate.

[0223] Examples of the polyisocyanate used for the amination reaction include hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate, xylylene diisocyanate, diisocyanates obtained by hydrogenating aromatic isocyanates among these diisocyanates (for example, diisocyanates such as hydrogenated toluene diisocyanate and hydrogenated xylene diisocyanate), di- or tri-polyisocyanates such as triphenylmethane triisocyanate and dimethylene triphenyl triisocyanate, and polyisocyanates obtained by polymerizing diisocyanates.

[0224] As the polyols used for the urethanization reaction, generally, in addition to aromatic, aliphatic and alicyclic polyols, polyester polyols, polyether polyols and the like can be used.

[0225] Examples of the aliphatic and alicyclic polyols include 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, ethylene glycol, propylene glycol, trimethylolethane, trimethylolpropane, dimethylolheptane, dimethylolpropionic acid, dimethylolbutyric acid, glycerin, and hydrogenated bisphenol A.

[0226] As polyester polyol, compounds obtained by dehydration condensation reaction of the above-mentioned polyols and polycarboxylic acids can be cited. As specific compounds of polycarboxylic acids, succinic acid, adipic acid, maleic acid, trimellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, etc. can be cited. These polycarboxylic acids can also be anhydrides.

[0227] Examples of the polyether polyol include, in addition to polyalkylene glycol, polyoxyalkylene-modified polyols obtained by reacting the above-mentioned polyols or phenols with an alkylene oxide.

[0228] The above-mentioned multifunctional polyester (meth) acrylate oligomer can be obtained by a dehydration condensation reaction using (meth) acrylic acid, a polycarboxylic acid and a polyol. As the polycarboxylic acid used for the dehydration condensation reaction, succinic acid, adipic acid, maleic acid, itaconic acid, trimellitic acid, pyromellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, etc. can be listed. These polycarboxylic acids can also be anhydrides. In addition, as the polyol used for the dehydration condensation reaction, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, dimethylol heptane, dimethylol propionic acid, dimethylol butyric acid, trimethylol propane, di-trimethylol propane, pentaerythritol, dipentaerythritol, etc. can be listed.

[0229] The polyfunctional epoxy (meth)acrylate oligomer can be obtained by an addition reaction of polyglycidyl ether and (meth)acrylic acid. Examples of the polyglycidyl ether include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and bisphenol A diglycidyl ether.

[0230] The hard coat layer may contain one or two or more (meth)acrylic oligomers.

[0231] [Surface modifier]

[0232] Surface modifiers are substances such as leveling agents, antistatic agents, surfactants, water-repellent and oil-repellent agents, inorganic particles, and organic particles that can change the surface properties of the hard coating.

[0233] Examples of the leveling agent include polyether-modified polyalkylsiloxane, polyether-modified silicone, polyester-modified hydroxyl-containing polyalkylsiloxane, polyether-modified polydimethylsiloxane having an alkyl group, modified polyether, and silicone-modified acrylic.

[0234] Examples of the antistatic agent include glycerin fatty acid ester monoglyceride, glycerin fatty acid ester organic acid monoglyceride, polyglycerin fatty acid ester, sorbitan fatty acid ester, cationic surfactants, and anionic surfactants.

[0235] Examples of the surfactant and the water- and oil-repellent agent include fluorine-containing surfactants and water- and oil-repellent agents such as oligomers containing a fluorine-containing group-lipophilic group and oligomers containing a fluorine-containing group-hydrophilic group-lipophilic group-UV reactive group.

[0236] Examples of the inorganic particles include silica particles, alumina particles, zirconia particles, silicon particles, silver particles, and glass particles.

[0237] Examples of the organic particles include acrylic particles and silicon particles.

[0238] The hard coat layer may contain one or more surface modifiers.

[0239] [Photopolymerization initiator]

[0240] As the photopolymerization initiator, monofunctional photopolymerization initiators can be cited. Specifically, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone [Darocure 2959: manufactured by Merck]; α-hydroxy-α,α'-dimethylacetophenone [Darocure 1173: manufactured by Merck]; acetophenone-based initiators such as methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone [Irgacure 651], and 1-hydroxy-cyclohexyl phenyl ketone; benzoin ether-based initiators such as benzoin ethyl ether and benzoin isopropyl ether; and halogenated ketones, acylphosphine oxides, acylphosphonates, etc. These photopolymerization initiators can be used alone or in combination of two or more.

[0241] [UV absorber]

[0242] Examples of the UV absorber include hydroxyphenyltriazine-based, benzotriazole-based, and benzophenone-based UV absorbers. The UV absorber may be used alone or in combination of two or more.

[0243] [Composition of hard coating]

[0244] The film thickness of the hard coating is preferably 1 to 40 μm, more preferably 2 to 10 μm. When the film thickness of the hard coating is 1 μm or more, sufficient hardness can be obtained, so it is preferred. On the other hand, when the film thickness of the hard coating is 40 μm or less, cracks can be suppressed during bending, so it is preferred. It should be noted that the film thickness of the hard coating can be measured by observing the cross section using a microscope or the like and measuring from the coating interface to the surface.

[0245] The pencil hardness of the hard coating surface is preferably HB or more, more preferably H or more, further preferably 2H or more, and particularly preferably 2H to 3H. It should be noted that the pencil hardness of the hard coating is the result of evaluation using a pencil scratch hardness test based on JIS K 5600-5-4: 1999. Specifically, the pencil is pressed against the surface of the hard coating at an angle of 45 degrees and a load of 750 g with gradually increasing hardness, and the hardest pencil that does not produce a scratch is evaluated as the pencil hardness.

[0246] By having a concavoconvex shape in the hard coat layer, an anti-glare laminate having excellent anti-glare properties and touch can be obtained. Specifically, the arithmetic mean roughness (Ra), maximum peak height (Rp), maximum valley depth (Rv) and skewness (Rsk) of the hard coat layer satisfy the following formulas (1) to (3). It should be noted that in this specification, the arithmetic mean roughness (Ra), maximum peak height (Rp), maximum valley depth (Rv) and skewness (Rsk) are measured according to the JIS B0601 1994 cutoff value of 0.8.

[0247] 0.03<Ra<0.10 (1)

[0248] 0.15<Rp / Rv<0.30 (2)

[0249] -5.0<Rsk<-2.0 (3)

[0250] Regarding the above formula (1), the arithmetic mean roughness (Ra) is an indicator of anti-glare properties. When Ra is less than 0.03, light scattering is insufficient, and thus anti-glare properties are insufficient. On the other hand, when Ra is greater than 0.10, light scattering is excessive and whitening occurs, and the texture also deteriorates. Formula (1) more preferably satisfies 0.035<Ra<0.095, and further preferably satisfies 0.040<Ra<0.92.

[0251] Regarding the above formula (2), Rp / Rv represents that the valley of the concavo-convex shape of the hard coat layer is deeper than the height of the peak, and is an indicator for maintaining a balance between anti-glare properties and finger slip properties. When Rp / Rv is 0.15, the anti-glare properties decrease. On the other hand, when Rp / Rv is 0.30 or more, the finger slip properties deteriorate. Formula (2) more preferably satisfies 0.16<Rp / Rv<0.29, and further preferably satisfies 0.17<Rp / Rv<0.28.

[0252] Regarding the above formula (3), the skewness (Rsk) is an index indicating the symmetry between the hill and valley. When the skewness (Rsk) is a negative value, it means that there are more valleys. When the skewness (Rsk) is within the range of formula (3), the valleys of the concave-convex shape are more than the hills, and the balance between anti-glare and finger sliding properties can be maintained. Formula (3) more preferably satisfies -4.8<Rsk<-2.5.

[0253] In addition, for the hard coating, a tactile contact is used as a contact, and the dynamic friction coefficient (μk) obtained by measuring with a load of 50g, a scanning speed of 10mm / second, and a scanning distance of 90mm satisfies the following formula (4). Among them, unlike the commonly used felt or needle-shaped contacts, the tactile contact used in this measurement method is a contact that imitates a human finger, so it is possible to quantitatively evaluate the finger sliding property. Among them, the above-mentioned dynamic friction coefficient (μK) is specifically measured according to the method described in the embodiment.

[0254] 0.6<μk<0.7 (4)

[0255] Regarding the above formula (4), the dynamic friction coefficient (μk) is an index of finger sliding property. When the dynamic friction coefficient (μk) is within the range of formula (4), appropriate finger sliding property can be obtained.

[0256] When the hard coating layer satisfies the above formulas (1) to (3), a concavo-convex shape with excellent anti-glare properties can be mainly formed. In addition, when the hard coating layer satisfies the above formula (4), excellent finger slip properties can be mainly formed. As a result, an anti-glare laminate with excellent anti-glare properties and touch can be obtained.

[0257] In one embodiment, the hard coating layer preferably has a reflectance (SCI) of 550 nm including regular reflected light. 550 ) and the reflectivity after removing the regular reflected light (SCE 550 ) satisfies the following formula (5). It should be noted that, in this specification, the reflectivity of regular reflected light (SCI 550 ) and the reflectivity after removing the regular reflected light (SCE 550 ) can be measured using a spectrophotometer SD7000 (manufactured by Nippon Denshoku). In addition, by performing a black treatment on the back surface using black spraying, the back surface reflection can be suppressed, and only the surface reflection can be measured.

[0258] 0.25<SCE 550 / SCI 550 <0.60 (5)

[0259] Regarding the above formula (5), SCE 550 / SCI 550 It is an indicator of the performance of preventing reflection. 55o / SCI 550 When it is greater than 0.25, light can be appropriately scattered, and the anti-glare property becomes high, which is preferred. 550 / SCI 550 When the value is less than 0.60, light scattering is not excessive and whitening can be prevented, thereby obtaining a suitable texture, which is preferred.

[0260] [Method for forming hard coat layer]

[0261] The method for forming the hard coat layer is not particularly limited, and the hard coat layer can be formed, for example, by applying a hard coat liquid on a layer (eg, a high-hardness resin layer) below the hard coat layer and then photopolymerizing the hard coat layer.

[0262] The method for applying the hard coating liquid (polymerizable composition, reactive composition) is not particularly limited, and known methods can be used. For example, spin coating, dip coating, spray coating, slide coating, rod coating, roller coating, gravure coating, meniscus coating, flexographic printing, screen printing, pat coating, brush coating, etc. can be mentioned.

[0263] As the lamp used for light irradiation in photopolymerization, a lamp having a light emission distribution below 420 nm in wavelength can be used. Examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc. Among them, high-pressure mercury lamps or metal halide lamps efficiently emit light in the active wavelength region of the initiator, and in most cases do not emit short-wavelength light that reduces the viscoelastic properties of the obtained polymer due to crosslinking, and long-wavelength light that heats and evaporates the reaction composition, and are therefore preferred.

[0264] The irradiation intensity of the lamp is a factor that affects the degree of polymerization of the obtained polymer and can be appropriately controlled according to the performance of each target product. In the case of a conventional cleavage-type initiator having an acetophenone group, the irradiation intensity is preferably 0.1 to 300 mW / cm 2 It is particularly preferred to use a metal halide lamp with an illumination of 10 to 40 mW / cm 2 .

[0265] Photopolymerization reaction is inhibited by oxygen in the air or oxygen dissolved in the reactive composition. Therefore, it is desirable to perform light irradiation using a method that can eliminate the reaction inhibition caused by oxygen. As one such method, there is a method in which the reactive composition is covered with a film made of polyethylene terephthalate or Teflon to block contact with oxygen, and light is irradiated to the reactive composition through the film. Alternatively, light can be irradiated to the composition through a light-transmitting window in an inert atmosphere in which oxygen is replaced with an inert gas such as nitrogen or carbon dioxide.

[0266] When light irradiation is performed under an inert atmosphere, a certain amount of inert gas is usually introduced in order to keep the atmospheric oxygen concentration at a low level. Due to the introduction of the inert gas, an airflow is generated on the surface of the reactive composition, causing the monomer to evaporate. In order to suppress the level of monomer evaporation, the airflow velocity of the inert gas is preferably less than 1 m / sec, more preferably less than 0.1 m / sec, in terms of the relative velocity relative to the laminate coated with the hard coating liquid moving under the inert gas atmosphere. By making the airflow velocity within the above range, the monomer evaporation caused by the airflow can be substantially suppressed.

[0267] In order to improve the adhesion of the hard coat layer, the coated surface is sometimes pre-treated. Examples of treatments include known methods such as sandblasting, solvent treatment, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet treatment, and primer treatment using a resin composition.

[0268] There are no particular restrictions on the method of forming the concavoconvex on the hard coating layer (anti-glare treatment), but a method using a mold is preferred. For example, the following method can be cited: first, a high-hardness resin layer, a coating obtained by coating a reactive composition, and a mold are stacked in sequence; then, the reactive composition is photopolymerized and then demolded. The photopolymer (hard coating layer) of the reactive composition has a shape reflecting the rough surface of the mold on the contact surface with the mold. That is, it is a method of performing an anti-glare treatment of the hard coating layer by transfer using a mold.

[0269] As long as the mold can transmit UV light, there is no particular limitation, and glass, transparent resin, etc. can be used. In one embodiment, the mold can be a mold formed by laminating a transparent film and a transparent resin with a rough surface. As the transparent film, a PET film can be cited. As the transparent resin with a rough surface, acrylic resin, etc. can be cited. At this time, the rough surface of the transparent resin is not particularly limited, and it can be a rough surface formed by adding particles (organic particles, inorganic particles, etc.) to the transparent resin, or it can be a rough surface formed by etching the transparent resin, or it can be a rough surface formed by printing and curing the transparent resin. The shape of the rough surface is not particularly limited, and from the perspective of being used for liquid crystal panels, etc., it is preferably a pattern. By controlling the type of mold used (material, surface haze, thickness, shape, etc.), the amount of particles added, etc., the surface (concave and convex shape) of the hard coating layer can be controlled. Thus, a hard coating layer that satisfies the above-mentioned formulas (1) to (4) can be formed. In addition, it is preferred that a hard coating layer that also satisfies the above-mentioned formula (5) can be formed.

[0270] In the above-mentioned method for forming the hard coating layer, it is preferred to crimp a patterned PET film to transfer the concave-convex shape. That is, using one embodiment of the present invention, a method for manufacturing an anti-glare laminate can be provided. At this time, the above-mentioned manufacturing method includes the step of crimping a patterned PET film on the surface of the hard coating layer to transfer the concave-convex shape. Among them, as the patterned PET film, for example, PTH, PTHA and PTHZ of Emblet manufactured by UNITIKA, PF11 and PF23 of low-glare AG film manufactured by Daicel, etc. can be used.

[0271] <Physical properties of anti-glare laminate>

[0272] In one embodiment, the anti-glare laminate preferably has high shape stability. Specifically, after being kept for 120 hours under an environment of a temperature of 85°C and a relative humidity of 85%, the change in warpage is preferably 350 μm or less, more preferably 250 μm or less, further preferably 175 μm or less, and particularly preferably 75 μm or less. When the change in warpage is 350 μm or less, it can also be used appropriately in a high temperature and high humidity environment, and is therefore preferred. Furthermore, high shape stability can be obtained by using a high hardness resin layer. By interposing a high hardness resin layer between the substrate layer and the hard coating layer, the shape of the anti-glare laminate is stable even in a high temperature and high humidity environment. It should be noted that the shape stability can also be controlled by appropriately changing the material of the substrate layer and the hard coating layer, the difference in glass transition temperature (Tg) between the substrate layer and the high hardness resin layer, the difference in hardness, the difference in glass transition temperature (Tg) between the high hardness resin layer and the hard coating layer, the difference in hardness, etc.

[0273] <Application>

[0274] The above-mentioned anti-glare laminated body has excellent anti-glare properties and touch, so it can be used as a protective plate or front panel of a liquid crystal surface as described above. In one embodiment, a vehicle-mounted display device including an anti-glare laminated body is provided. In addition, in another embodiment, a touch panel front protective plate including an anti-glare laminated body is provided. Furthermore, in another embodiment, a front panel for OA equipment, portable electronic equipment or television is provided.

[0275] Example

[0276] Hereinafter, although the Example of this invention is illustrated, this invention is not limited to a form of an Example.

[0277] <Surface roughness measurement>

[0278] The surface of the hard coating layer having an uneven surface was measured for arithmetic mean roughness (Ra), maximum peak height (Rp), maximum valley depth (Rv), and skewness (Rsk) under the following conditions based on JIS B0601 1994 using a surface roughness measuring machine "SURFCOM480A" manufactured by Tokyo Seimitsu Co., Ltd.

[0279] [Surface roughness measurement conditions]

[0280] Cut-off value: 0.8mm;

[0281] Evaluation length: 5 times the length of the cutoff value;

[0282] Feed speed of stylus: 0.3mm / s;

[0283] Preparation length: 2 times the cutoff value.

[0284] <Measurement of dynamic friction coefficient>

[0285] The dynamic friction coefficient (μk) of the hard coat surface was measured under the following conditions using a static and dynamic friction measuring machine "TL201Tt" manufactured by Trinity-Lab.

[0286] [Dynamic friction coefficient measurement conditions]

[0287] Contact: tactile contact;

[0288] Load: 50g;

[0289] Scanning speed: 10mm / s;

[0290] Scanning distance: 90mm.

[0291] <Reflectivity measurement>

[0292] The reflectance including regular reflection light (SCI) and the reflectance excluding regular reflection light (SCE) of the hard coating layer were measured under the following conditions using a spectrophotometer "SD7000" manufactured by Nippon Denshoku Co., Ltd. The reflectance at a wavelength of 550 nm was taken as SCI and SCE. 550 、SCE 550 The back side was painted black to suppress reflections from the back side.

[0293] [Reflectivity measurement conditions]

[0294] Light source-field of view: D65 / 2°;

[0295] Measuring diameter: φ8mm (MAV);

[0296] Lighting and light-receiving conditions: di 8° (SCI), de 8° (SCE).

[0297] <SW hardness>

[0298] For the hard coat layer having a concavoconvex shape of the anti-glare laminate, steel wool #0000 manufactured by NIPPON STEEL WOOL CO., LTD. was used at a density of 100 g / cm 2 The load was reciprocated 15 times, and the damage at this time was visually observed and evaluated in 10 levels, which were recorded as RANK1 to RANK10. However, the measurement was performed twice, and if the results were different, the range was used as the measurement result.

[0299] RANK1: No scratches (same as inorganic glass);

[0300] RANK2: 1 to 5 scars;

[0301] RANK3: 6 to 10 scars;

[0302] RANK4: 11-15 scars;

[0303] RANK5: 16-20 scars;

[0304] RANK6: 21-25 scars;

[0305] RANK7: 26-30 scars;

[0306] RANK8: 31-40 scars;

[0307] RANK9: more than 41 scars (same as polymethacrylic acid);

[0308] RANK10: 41 or more scratches (same as polycarbonate).

[0309] <Shape stability>

[0310] The test piece (anti-glare laminate) is cut into 100mm×60mm. The cut test piece is placed on a two-point support type bracket and put into an environmental testing machine set at a temperature of 23% and a relative humidity of 50% for more than 24 hours. After the state is adjusted, the warping is measured (before treatment). Next, the test piece is placed on a bracket and put into an environmental testing machine set at a temperature of 85°C and a relative humidity of 85%, and kept in this state for 120 hours. Then, each bracket is moved in the environmental testing machine set at a temperature of 23% and a relative humidity of 50%, and after keeping this state for 4 hours, the warping is measured again (after treatment). The warping is measured using a three-dimensional shape measuring machine with an electric stage (KS-1000 manufactured by KEYENCE). The taken out test piece is horizontally set in an upward convex state, scanned at intervals of 1 mm, and the bulge in the center is measured as the warping. The absolute value of the difference in the warping amount before and after treatment, that is,

[0311] |(Warp amount after treatment) - (Warp amount before treatment)|

[0312] The shape stability was evaluated.

[0313] [Example 1]

[0314] <Laminate>

[0315] A synthetic resin laminate was formed using a multilayer extruder having a single screw extruder with a screw diameter of 35 mm, a single screw extruder with a screw diameter of 65 mm, a feed block connected to all the extruders, and a T-die connected to the feed block. Optimas 7500 manufactured by Mitsubishi Gas Chemical was continuously introduced as a high hardness resin (B1) into the single screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (manufactured by Mitsubishi Engineering-Plastics Co., Ltd., trade name: Iupilon S-1000) was continuously introduced into the single screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 280°C and a discharge rate of 50.0 kg / h. The feed block connected to all the extruders had two types of two-layer distribution pins, and the high hardness resin (B1) and the polycarbonate resin were introduced at a temperature of 270°C and laminated. The sheet was extruded into a sheet form by a T-die connected to the front thereof at a temperature of 270°C, and cooled while transferring the mirror surface by three mirror-finished rollers at temperatures of 120°C, 130°C, and 190°C from the upstream side, to obtain a laminate of a high-hardness resin (B1) layer (high-hardness resin layer) and a polycarbonate resin layer (base material layer). The thickness of the obtained laminate was 1.0 mm, and the thickness of the high-hardness resin (B1) layer was 60 μm near the center.

[0316] Among them, Optimas 7500 manufactured by Mitsubishi Gas Chemical used as the high hardness resin (B1) is a copolymer resin containing a (meth)acrylate structural unit (a) represented by the above general formula (1) and an aliphatic vinyl structural unit (b) represented by the above general formula (2). In this case, the total ratio of the above (meth)acrylate structural unit (a) and the above aliphatic vinyl structural unit (b) is 99 mol% of the total structural units of the above copolymer resin, and the ratio of the above (meth)acrylate structural unit (a) is 75 mol% of the total structural units of the above copolymer resin.

[0317] <Photocurable resin composition (Y-1)>

[0318] A mixture of 60 mass % of U6HA (hexafunctional urethane acrylate oligomer, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), 35 mass % of #260 (1,9-nonanediol diacrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.), and 5 mass % of a fluorine-based leveling agent was set to 100 mass parts, and 3 mass parts of a photoinitiator I-184 (manufactured by BASF Corporation [compound name: 1-hydroxy-cyclohexyl phenyl ketone]) was added to obtain a photocurable resin composition (Y-1).

[0319] <PET film with pattern (Z-1)>

[0320] 40 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Lightacrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 25 parts by mass of a silica dispersion (solid content 18%, Z-AGD-6, average particle size 2 μm, manufactured by AICA Industries) and 3 parts by mass of an external photoinitiator (trade name Omnirad184, manufactured by IGM Resins) were mixed and stirred with respect to 35 parts by mass of MEK to prepare a coating liquid (i). Next, the coating liquid (i) was applied on a PET (polyethylene terephthalate) film so that the dry film thickness became 2.5 μm, dried at 80° C. for 2 minutes, and then cured by irradiating ultraviolet light at a line speed of 1.5 m / min using a conveyor equipped with a high-pressure mercury lamp having a light source distance of 12 cm and an output of 80 W / cm, thereby preparing a patterned PET film (Z-1).

[0321] The photocurable resin composition (Y-1) was applied on the high hardness resin (B1) layer of the laminate of the high hardness resin (B1) layer (high hardness resin layer) and the polycarbonate resin layer (base material layer) using a bar coater so that the thickness of the cured coating film was 5 to 10 μm, and the patterned surface of the patterned PET film (Z-1) was covered and crimped in such a way that the patterned surface was in contact with the coating liquid. Thereafter, the film was cured by irradiation with a metal halide lamp (20 mW / cm) at a light source distance of 12 cm for 30 seconds, and the patterned PET film was peeled off to obtain an anti-glare laminate having a hard coating layer with concavoconvexities provided on the high hardness resin layer (B1).

[0322] [Example 2]

[0323] An anti-glare laminate was produced in the same manner as in Example 1 except that the following high hardness resin (B2) was used instead of the high hardness resin (B1).

[0324] The high hardness resin (B2) was prepared as follows. That is, 40% by mass of the high hardness resin (B1) and 60% by mass of XIBOND140 as a styrene-unsaturated dicarboxylic acid copolymer (C) were added and mixed for 30 minutes using a mixer. Next, melt kneading was performed at a barrel temperature of 230°C using an extruder with a screw diameter of 26 mm (manufactured by Toshiba Machinery, TEM-26SS, L / D≈40), and after extrusion into a strand shape, pelletization was performed using a pelletizer to obtain a resin composition (B2). The pelletization was performed stably.

[0325] [Example 3]

[0326] An anti-glare laminate was produced in the same manner as in Example 1 except that the following high hardness resin (B3) was used instead of the high hardness resin (B1).

[0327] The high hardness resin (B3) was prepared as follows. That is, 75% by mass of R-100 as a styrene-unsaturated dicarboxylic acid copolymer (E) and 25% by mass of methyl methacrylate resin Parapet HR-L as a resin containing a vinyl monomer (D) were added and mixed for 30 minutes using a mixer. Next, melt kneading was performed at a barrel temperature of 230°C using an extruder with a screw diameter of 26 mm (manufactured by Toshiba Machine, TEM-26SS, L / D≈40), and after extrusion into a strand shape, pelletization was performed using a pelletizer to obtain a high hardness resin (B3). The pelletization was performed stably.

[0328] [Example 4]

[0329] An anti-glare laminate was produced in the same manner as in Example 1 except that the following high hardness resin (B4) was used instead of the high hardness resin (B1).

[0330] The high hardness resin (B4) was prepared as follows. That is, 75% by mass of a copolymer (RESISFYR100 (manufactured by Denka)) containing 21% by mass of methyl methacrylate structural units, 64% by mass of styrene structural units and 15% by mass of maleic anhydride structural units as a styrene-unsaturated dicarboxylic acid copolymer (E) and 25% by mass of a copolymer (DELPETPM-120N (manufactured by Asahi Kasei) containing 7% by mass of styrene structural units, 86% by mass of methyl methacrylate structural units and 7% by mass of N-phenylmaleimide structural units as a resin copolymer (G) were added and mixed with a mixer for 30 minutes. Then, melt kneading was performed at a barrel temperature of 230°C using an extruder with a screw diameter of 26 mm (TEM-26SS manufactured by Toshiba Machine, L / D≈40), and after extrusion into a strand shape, pelletization was performed using a pelletizer to obtain a high hardness resin (B4) which is an alloy of the resin copolymer (G) and the styrene-unsaturated dicarboxylic acid copolymer (E). Granulation proceeds stably.

[0331] [Example 5]

[0332] An anti-glare laminate was manufactured in the same manner as in Example 1, except that Iupilon KH3410UR (a polycarbonate resin of bisphenol C, manufactured by Mitsubishi Engineering-Plastics Corporation) was used as the high hardness resin (B5) instead of the high hardness resin (B1), and the barrel temperature of the single-screw extruder with a screw diameter of 35 mm for introducing the high hardness resin (B5) was changed from 240°C to 270°C.

[0333] [Example 6]

[0334] An anti-glare laminate was produced in the same manner as in Example 1 except that the following high hardness resin (B6) was used instead of the high hardness resin (B1).

[0335] The high hardness resin (B6) was prepared as follows. That is, 50% by mass of XIBOND160 as a styrene-unsaturated dicarboxylic acid copolymer (C) and 50% by mass of methyl methacrylate resin Parapet HR-L as a resin containing a vinyl monomer (D) were added and mixed in a mixer for 30 minutes. Next, melt-kneading was performed at a barrel temperature of 230°C using an extruder with a screw diameter of 26 mm (manufactured by Toshiba Machine, TEM-26SS, L / D≈40), and after extrusion into a strand shape, pelletization was performed using a pelletizer to obtain a high hardness resin (B6). The pelletization was performed stably.

[0336] [Example 7]

[0337] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-2) was used instead of the patterned PET film (Z-1).

[0338] <PET film with pattern (Z-2)>

[0339] The following coating liquid (ii) was used instead of the coating liquid (i) to prepare a patterned PET film (Z-2).

[0340] Relative to 10 parts by mass of MEK, 40 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Lightacrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 50 parts by mass of a silica dispersion (solid content 18%, Z-AGD-6, average particle size 2 μm, manufactured by AICA Industries Co., Ltd.) and 3 parts by mass of an external photoinitiator (trade name Omnirad184, manufactured by IGM Resins) were mixed and stirred to prepare the above-mentioned coating solution (ii).

[0341] [Example 8]

[0342] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-3) was used instead of the patterned PET film (Z-1).

[0343] <PET film with pattern (Z-3)>

[0344] The following coating liquid (iii) was used instead of the coating liquid (i) to prepare a patterned PET film (Z-2).

[0345] The coating solution (ii) is prepared by mixing and stirring 40 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Lightacrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 60 parts by mass of a silica dispersion (solid content 18%, Z-AGD-6, average particle size 2 μm, manufactured by AICA Industries, Ltd.) and 3 parts by mass of an external photoinitiator (trade name Omnirad184, manufactured by IGM Resins).

[0346] [Example 9]

[0347] An anti-glare laminate was produced in the same manner as in Example 1 except that methyl methacrylate resin Parapet HR-L (manufactured by Kuraray, weight average molecular weight: 90,000, pencil hardness: 2H) was used instead of the high hardness resin (B1).

[0348] [Comparative Example 1]

[0349] An antiglare laminate was produced in the same manner as in Example 1 except that Cosmoshine (registered trademark) A-4100 (PET film, thickness: 100 μm, haze: 0.9%, manufactured by Toyobo Co., Ltd.) (Z-4) was used instead of the patterned PET film (Z-1).

[0350] [Comparative Example 2]

[0351] An antiglare laminate was produced in the same manner as in Example 1 except that PS-27 (PET film, thickness: 100 μm, haze 34%, manufactured by Daicel) (Z-5) was used instead of the patterned PET film (Z-1).

[0352] [Comparative Example 3]

[0353] An anti-glare laminate was produced in the same manner as in Example 1 except that a hard coat layer was formed as follows.

[0354] That is, with respect to 50 parts by mass of MEK, 50 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, product: Lightacrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), silica particles (octylsilane-treated pyrogenic silica, average primary particle size 1.9 μm, product name: SE6050-SYB, manufactured by Admatechs Co., Ltd.) and 3 parts by mass of a photoinitiator (product name: IRGACURE 184, manufactured by Toyotsu Chemical Plastics Co., Ltd.) are mixed and stirred to prepare a photocurable composition (Y-2).

[0355] The photocurable composition (Y-2) was applied to the high hardness layer of the laminate (X-1) using a bar coater so that the thickness of the cured coating was 2.5 μm, and dried at 80° C. for 2 minutes. The coating was cured by irradiation with a metal halide lamp (20 mW / cm) at a light source distance of 12 cm for 30 seconds while nitrogen purging to obtain an anti-glare laminate.

[0356] The anti-glare laminates obtained in Examples 1 to 9 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0357] [Table 1]

[0358]

[0359] In Examples 1 to 9 and Comparative Examples 1 to 3, the arithmetic mean roughness (Ra), maximum peak height (Rp), maximum valley depth (Rv), Rp / Rv, skewness (Rsk), dynamic friction coefficient (μk), SCI 500 、SCE 500 、SCE 550 / SCI 500 , SW hardness and shape stability. The obtained results are shown in Table 2 below.

[0360] [Table 2]

[0361]

[0362] As is also clear from the results in Table 2, Examples 1 to 9 have excellent anti-glare properties and tactile feel because Ra, Rp / Rv and Rsk satisfy equations (1) to (3) and μK satisfies equation (4). 500 / SCI 500 Since the formula (5) is satisfied, it is confirmed that the anti-glare property is excellent. In addition, it is confirmed that Examples 1 to 8 using the high-hardness resins (B1) to (B6) are also excellent in shape stability.

[0363] On the other hand, in Comparative Example 1, since Rp / Rv and Rsk do not satisfy equations (2) and (3), and μK does not satisfy equation (4), the anti-glare property and touch feeling are insufficient. 500 / SCI 500 If the formula (5) is not satisfied, the anti-glare property will be insufficient.

[0364] In addition, in Comparative Example 2, since Ra and Rp / Rv do not satisfy equations (1) and (2), and μK does not satisfy equation (4), the anti-glare property and touch feel are insufficient. 500 / SCI 500 If the formula (5) is not satisfied, the anti-glare property will be insufficient.

[0365] Furthermore, in Comparative Example 3, since Ra, Rp / Rv and Rsk do not satisfy the equations (1) to (3), and μK does not satisfy the equation (4), the anti-glare property and touch feel are insufficient. 500 / SCI 500 Although the expression (5) was satisfied, it was confirmed that the SW hardness was insufficient because the hard coat layer contained silica fine particles.

Claims

1. An anti-glare laminate, comprising at least a substrate layer containing a polycarbonate resin a1, a high-hardness resin layer containing a high-hardness resin, and a hard coating layer, in this order, characterized in that: The arithmetic mean roughness Ra, maximum peak height Rp, maximum valley depth Rv and skewness Rsk of the hard coating satisfy the following equations (1) to (3): 0.03 <Ra<0.1 0 (1) 0.15<Rp / Rv<0.30 (2) -5.0<Rsk<-2.0(3), The dynamic friction coefficient μk obtained by using a tactile probe as the probe of the hard coating and measuring the hard coating at a load of 50 g, a scanning speed of 10 mm / sec, and a scanning distance of 90 mm satisfies the following formula (4): 0.6<μk<0.7 (4), The high-hardness resin is a resin having a pencil hardness of HB or more as measured by a pencil scratch hardness test based on JIS K 5600-5-4:1999. The arithmetic mean roughness Ra, the maximum peak height Rp, the maximum valley depth Rv and the skewness Rsk are obtained by measuring the surface of the hard coating layer having an uneven surface under the following conditions based on JIS B06011994 using a surface roughness measuring machine SURFCOM 480A manufactured by Tokyo Seimitsu Co., Ltd., The surface roughness test conditions are: Cut-off value: 0.8mm; Evaluation length: 5 times the length of the cutoff value; Feed speed of stylus: 0.3mm / s; Preparation length: 2 times the cutoff value.

2. The anti-glare laminate according to claim 1, wherein: The reflectivity SCI of the hard coating layer including regular reflected light at a wavelength of 550nm 550 and the reflectivity SCE excluding the regular reflected light 550 Satisfies the following formula (5): 0.25<SCE 550 / SCI 550 <0.60 (5), The reflectivity SCI of the regular reflected light 550 and the reflectivity SCE after removing the regular reflected light 550 The color was obtained by measuring using a spectrophotometer SD7000 manufactured by Nippon Denshoku Co., Ltd. under the following conditions: The reflectivity was measured under the following conditions: Light source-field of view: D65 / 2°; Measuring diameter: MAV, φ8mm; Lighting and light-receiving conditions: SCI, di 8°; SCE, de 8°.

3. The anti-glare laminate according to claim 1 or 2, wherein: The anti-glare laminate has a warpage change of 350 μm or less after being kept in an environment of a temperature of 85° C. and a relative humidity of 85% for 120 hours. The change in warpage is determined as follows, The anti-glare laminated body used as a test piece was cut into 100 mm × 60 mm, and the cut test piece was placed on a two-point support type bracket, and put into an environmental testing machine set at a temperature of 23% and a relative humidity of 50% for more than 24 hours. After the state was adjusted, the warpage was measured as the warpage before treatment; then, the test piece was placed on a bracket, put into an environmental testing machine set at a temperature of 85°C and a relative humidity of 85%, and kept in this state for 120 hours, and then each bracket was moved in the environmental testing machine set at a temperature of 23% and a relative humidity of 50%, and after keeping in this state for 4 hours, the warpage was measured again as the warpage after treatment; the warpage was measured using KS-1000 manufactured by KEYENCE, which is a three-dimensional shape measuring machine with an electric stage, and the taken out test piece was horizontally set in an upward convex state, scanned at intervals of 1 mm, and the bulge in the central part was measured as the warpage; the absolute value of the difference in the warpage amount before and after treatment shown in the following formula was taken as the change in the warpage, |(amount of warping after treatment) - (amount of warping before treatment)|.

4. The anti-glare laminate according to claim 1 or 2, wherein: The high-hardness resin layer has a thickness of 10 to 250 μm.

5. The anti-glare laminate according to claim 1 or 2, wherein: The total thickness of the base material layer and the high-hardness resin layer is 100 to 3,000 μm.

6. The anti-glare laminate according to claim 1 or 2, wherein: The high-hardness resin B includes at least one selected from the group consisting of resin B1, resin B2, resin B3, resin B4, resin B5, and resin B6. The resin B1 is a copolymer resin comprising a (meth)acrylate structural unit a represented by the following general formula (1) and an aliphatic vinyl structural unit b represented by the following general formula (2), wherein the total ratio of the (meth)acrylate structural unit a and the aliphatic vinyl structural unit b is 90 to 100 mol% of the total structural units of the copolymer resin, and the ratio of the (meth)acrylate structural unit a is 65 to 80 mol% of the total structural units of the copolymer resin, wherein: In formula (1), R 1 is a hydrogen atom or a methyl group, R 2 is an alkyl group having 1 to 18 carbon atoms, In formula (2), R 3 is a hydrogen atom or a methyl group, R 4 is a cyclohexyl group having a hydrocarbon group having 1 to 4 carbon atoms or a cyclohexyl group having no substituent, The resin B2 comprises 35 to 65% by mass of the resin B1 and 35 to 65% by mass of a styrene-unsaturated dicarboxylic acid copolymer C, wherein the styrene-unsaturated dicarboxylic acid copolymer C comprises 65 to 90% by mass of a styrene structural unit c1 and 10 to 35% by mass of an unsaturated dicarboxylic anhydride structural unit c2. The resin B3 comprises 55 to 10% by mass of a resin D containing a vinyl monomer, and 45 to 90% by mass of a styrene-unsaturated dicarboxylic acid copolymer E, wherein the styrene-unsaturated dicarboxylic acid copolymer E comprises 50 to 80% by mass of a styrene structural unit e1, 10 to 30% by mass of an unsaturated dicarboxylic acid structural unit e2, and 5 to 30% by mass of a vinyl structural unit e3. The resin B4 is a resin copolymer G containing 5 to 20% by mass of styrene structural units, 70 to 90% by mass of (meth)acrylate structural units, and 5 to 20% by mass of N-substituted maleimide structural units, or an alloy of the resin copolymer G and a styrene-unsaturated dicarboxylic acid copolymer E, The resin B5 comprises a structural unit H represented by the following general formula (3): The resin B6 comprises 35-65 mass % of a resin D containing a vinyl monomer and 35-65 mass % of a styrene-unsaturated dicarboxylic acid copolymer C. The styrene-unsaturated dicarboxylic acid copolymer C comprises 65-90 mass % of a styrene structural unit c1 and 10-35 mass % of an unsaturated dicarboxylic anhydride structural unit c2.

7. The anti-glare laminate according to claim 6, wherein: The resin B5 is a copolymer further comprising a structural unit J represented by the following general formula (4):

8. The anti-glare laminate according to claim 1 or 2, wherein: The hard coating layer does not contain organic particles and inorganic particles.

9. The anti-glare laminate according to claim 1 or 2, wherein: The polycarbonate resin a1 contains a component derived from a monohydric phenol represented by the following general formula (5): In the formula, R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, R 6 Each independently represents a hydrogen atom, a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which has a substituent, and n is an integer of 0 to 4, wherein the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms.

10. A vehicle-mounted display device, characterized in that: The present invention comprises the anti-glare laminate according to any one of claims 1 to 9.

11. A touch panel front protection plate, characterized in that: The present invention comprises the anti-glare laminate according to any one of claims 1 to 9.

12. A front panel for OA equipment, portable electronic equipment or television, characterized in that: The present invention comprises the anti-glare laminate according to any one of claims 1 to 9.

13. A method for producing the anti-glare laminate according to any one of claims 1 to 9, characterized in that: The method comprises the step of transferring the concavo-convex shape by pressing a patterned PET film onto the surface of the hard coat layer.

Citation Information

Patent Citations

  • Touch panel, display device, optical sheet, and optical sheet sorting method

    WO2017188186A1

  • Decorative sheet, decorative molded product and method for producing decorative molded product

    JP2017047595A

  • Anti-glare film, and manufacturing method and application of the same

    JP2019203931A